Implications Of Service-Based Learning Towards The Building Of Santri’S Social Care In Pondok Pesantren Darussalam Kediri And Pondok Pesantren Al Urwatul Wutsqo Jombang - Hasan, Moch. Sya’roni; Ch., Mufidah; Padil, Moh. (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2021)
his research aims to reveal the service-based learning (service learning) in social care building ofÂ santri (student) on Pondok Pesantren Al Urwatul Wustqo Jombang dan Darussalam Kediri, with a focus on covering the implication of service learning for social care building of student on Pondok Pesantren Al Urwatul Wutsqo Jombang and Sumbersari Kediri.This research employs a qualitative approach with a multisite study design. Data collection is carried out using in-depth interview, participant observation, and documentation. Data analysis techniques include data collection, data condensation, data presentation, and drawing conclusion. Checking the validity of the finding is carried out by extension of participation; triangulation technique of sources, theories, and methods; and persistence of observation. The research informants are the pesantren caretakers, the ustadzah (teachers), students and the society.The implication (impact) of service learning on Â caring character building of student is experiencing very positive changes. It proven by the research finding. Student who has participated in service learning has experienced change mainly in term of caring for others. This form of caring can be seen from several indicators as follows: they have compassion feeling whaen their friend is sick. Thus, they take care for that friend, the emergence of a sense of brotherhood, protect their friends from bullying the others, they are more sensitive to what is going on around them, they help without having to ask, their respect to the teacher increase.